The Politics of Selective Default: The Foreign Debts of the Confederate States of America - Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 2000)
The Confederate States of America floated two small bond issues in Europe during the American Civil War; cotton bonds that traded primarily in England and junk bonds in Amsterdam. The Confederacy serviced the cotton bonds for the duration of the war and defaulted on the junk bond issue. Evidently the South believed that the cotton bonds provided a financial incentive for England to intervene or give military support. This policy of selective default suggests that reputation spillovers across markets may be smaller than indicated in theoretical models of debt repayment (Cole and Kehoe, 1994).
Keywords: 330